Combined case record forms for collating obstetric outcomes in rare rheumatic diseases - Rajat Kharbanda; R Naveen; Durga Prasanna Misra; Vikas Agarwal; Latika Gupta (Indian Journal of Rheumatology)
Background: Evaluating the fertility and obstetric outcomes in women with rare rheumatic diseases is challenging as it needs to take into account various influencing factors. Aims and Objectives: The aim is to draft a structured case record form (CRF) for collating obstetric outcomes in rheumatic diseases Materials and Methods: Clinical CRFs were designed for inflammatory myositis, ANCA associated vasculitis, Takayasu arteritis and systemic sclerosis with the objectives in mind, taking into account disease characteristics, drugs administered, and the changes related to the pregnant state. The forms underwent four rounds of revision by two rheumatologists with trial runs on three patients each. The form was scrutinized for face validity, ambiguity and were designed to ease filling them in a busy outpatient setup. Results: The CRF forms for obstetric outcomes in patients were labelled as version 10.0, 11.0, 12.0, and 13.0 for myositis, AAV, TA, and SSc. Conclusion: Beginning with a well-designed CRF is the first step in collating proper data for research. This paper details the steps involved in the same for collating obstetric outcomes in tfour rare rheumatic illnesses.